Fast convergence of the Coiflet-Galerkin method for general elliptic BVPs - Akbari, Hani (Zielona Góra: Uniwersytet Zielonogórski)
We consider a general elliptic Robin boundary value problem. Using orthogonal Coifman wavelets (Coiflets) as basis functions in the Galerkin method, we prove that the rate of convergence of an approximate solution to the exact one is O(2?nN) in the H1 norm, where "n" is the level of approximation and "N" is the Coiflet degree. The Galerkin method needs to evaluate a lot of complicated integrals.
Keywords: general stationary elliptic BVPs; Robin boundary condition; orthogonal Coifman wavelets; trivariate connection coefficients; fast convergence